Supplemental Parenteral Vitamin E Into Conventional Soybean Lipid Emulsion Does Not Prevent Parenteral Nutrition–Associated Liver Disease in Full‐Term Neonatal Piglets. (12th October 2015) - Muto, Mitsuru; Lim, David; Soukvilay, Amanda; Field, Catherine; Wizzard, Pamela R.; Goruk, Susan; Ball, Ronald O.; Pencharz, Paul B.; Mi, Si; Curtis, Jonathan; Wales, Paul W.; Turner, Justine M.
Abstract : Background: Parenteral nutrition–associated liver disease (PNALD) continues to cause morbidity and mortality for neonates with intestinal failure. Lipid peroxidation is one potential etiological factor. This study was designed to test if supplementing vitamin E into conventional soy‐based lipid would reduce the risk of PNALD. Methods: Sixteen piglets, aged 2–5 days and weighing 1.8–2.5 kg, were randomized to parenteral nutrition (PN) with soy lipid (SO, n = 8) or the same lipid plus α‐tocopherol, the most bioactive form of vitamin E (SO+E, n = 8). After 17 days, bile flow, liver chemistry, gene expression associated with bile acid metabolism, and bile acid composition were assessed. C‐reactive protein (CRP) and oxidative stress markers, including plasma 8‐isoprostane, were measured. All results were compared with a sow‐reared control group (CON). Results: Comparing PN‐treated groups, SO vs SO+E mean bile flow (5.91 vs 5.54 µL/g liver; P = .83), serum bile acid concentration (39.2 vs 26.6 µmol/L; P = .12), and total bilirubin (35.2 vs 26.9 µmol/L; P = .56) were not different. Gene expression related to bile acid metabolism and bile composition was not different between PN groups. There was no difference in CRP (41.8 vs 36.8 µg/mL; P = .22) or in plasma 8‐isoprostane (27.9 vs 26.1 pg/mL; P = .77). Conclusions: In term neonatal piglets, supplemental vitamin E did not prevent cholestasis. Additional vitamin E was not associated with reduced inflammation or oxidative stress. The benefit of supplementing vitamin E into conventional lipid, vs adding fish oil, to prevent early onset of PNALD requires further clarification.